Metaphorical Analysis and the Meaning of the Song “Another One Bite the Dust” by Queen - Adristi Yajna Zulaika; Chairinnisa Artanti; Cut Putri Alivia; Dira Annisa; Dian Marisha Putri (Universitas Muhammadiyah Enrekang, 2023)
A metaphor is a figure of speech that contrasts two unrelated items and helps in the communication of complex ideas or emotions by drawing on familiar or concrete concepts. Metaphor is often utilized in poetry, novels, films, songs, and so on. This study provides a metaphorical analysis of the lyrics to